2013
DOI: 10.4162/nrp.2013.7.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary patterns and hypertension among Korean adults: the Korean National Health and Nutrition Examination Survey (2008-2010)

Abstract: The objective of this study is to identify the dietary patterns associated with the risk of hypertensions among Korean adults using data from the Korean National Health and Nutrition Examination Survey (KNHANES, 2008-2010). This study analyzes data from 11,883 subjects who participated in the health and nutrition survey, aging from 20 to 64 years. We performed factor analysis based on the weekly mean intake frequencies of 36 food groups to identify major dietary patterns. We identified three major dietary patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 51 publications
6
20
1
2
Order By: Relevance
“…Our results were inconsistent with some previous studies [17,27], which reported the positive associations between red and processed meat and the risk of hypertension. There are several plausible explanations that may explain this null association.…”
Section: Disscussioncontrasting
confidence: 99%
“…Our results were inconsistent with some previous studies [17,27], which reported the positive associations between red and processed meat and the risk of hypertension. There are several plausible explanations that may explain this null association.…”
Section: Disscussioncontrasting
confidence: 99%
“…Dietary Pattern 1 in the current study, was characterised by energy-dense, nutrient-poor foods and is similar to the Western dietary pattern described by other researchers [16,19]. While this pattern is also associated with higher sodium and higher energy, we did not observe any relationship with BP.…”
Section: Discussionsupporting
confidence: 87%
“…Other dietary patterns observed to be inversely associated with blood pressure include a 'vegetable dietary pattern' in Japanese women [14], a 'fruit and milk dietary pattern' in Chinese men [15], 'dairy and carbohydrate pattern' in Korean adults [16], a 'cosmopolitan dietary pattern' in Dutch adults [17], a 'vegetables and dairy pattern 'or 'ethnic foods and alcohol dietary pattern' in British adults [18], and a 'healthy dietary pattern' in adult American Indians [19]. In addition, several dietary patterns have also been identified to be positively associated with blood pressure, including a 'meat dietary pattern' in Chinese men [15], a 'traditional dietary pattern' in Korean [16] and Dutch adults [17], and a 'Western dietary pattern' in Korean adults [16] and adult American Indians [19]. A recent systematic review and meta-analysis of the effect of dietary patterns on BP in adults, which included 5014 participants, found that the DASH, Mediterranean and Nordic diets all significantly reduced both SBP and DBP [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the authors ensured methodological strictness by selecting two other cut-offs (≥ |0.20| and ≥ |0.25|) that are also commonly applied in dietary pattern studies 34,35,36,37,38,39,40,44,45,46,47,48,49 .…”
Section: Discussionmentioning
confidence: 99%